Failure Analysis and Mechanism Research of Abnormal Stopping of a Certain Type of Aero-Engine - Su Baoquan, Zhou Deyuan, He Jie (Hangkong bingqi)
Regarding the failure of a certain type of unmanned aerial vehicle (UAV) crashing due to abnormal engine shutdown during its flight, in order to determine the cause of the failure, studies encompassing data analysis, fault localization, mechanism analysis, and fault reproduction are carried out around the engine body, fuel system, and engine control system. The results indicated that because of the considerable difference in thermal expansion coefficients among materials, the voltage regulator diode in the engine ignition control box experienced fatigue cracking at the welding part between the internal chip and the molybdenum column under the tensile stress of high-temperature epoxy resin, generating a gap. This resulted in the failure of the thyristor to open during the discharge process, preventing the high-voltage coil from generating voltage, causing ignition failure and resulting in a decrease in engine speed and subsequent shutdown. Finally, solutions are proposed, effectively addressing the practical problem and providing technical support for the performance testing of this type of UAV and the efficiency evaluation of the engine.